Batas Kolaborasi AI dan Manusia dalam Marketing Negotiation: Peran Budaya di Indonesia - Chairun Niza; Denny Lesmana Putra; Nuradini Ayuningtyas (Lembaga Teewan Journal Solutions, 2026)
This study aims to explore the boundaries of collaboration between humans and Artificial Intelligence (AI) in marketing negotiations by examining the role of Indonesian culture in shaping negotiation effectiveness. AI has evolved from an operational support tool into a strategic decision-making instrument capable of analyzing market data, predicting counterpart behavior, and optimizing negotiation strategies. However, marketing negotiation involves not only analytical processes but also trust, empathy, interpersonal communication, and cultural understanding. This study employs a qualitative approach within an interpretive constructivist paradigm to understand practitioners’ perceptions of the strengths and limitations of AI in negotiation. The research focuses on the Indonesian business culture, which is collectivistic, relationship-oriented, and characterized by high-context communication. The findings indicate that AI contributes significantly to analytical, predictive, and decision-support functions. Nevertheless, its ability to understand tacit knowledge, emotional cues, social context, and trust-building processes remains limited. Therefore, marketing negotiation effectiveness is better achieved through a complementary collaboration between humans and AI rather than full technological substitution. The study highlights culture as a key factor in determining the practical boundaries of AI implementation and underscores the importance of human relational capabilities in Indonesian business negotiations.